On posthuman war : computation and military violence - Hill, Mike, 1964- (University of Minnesota Press, 2022)
"Mike Hill delivers insights on the latest war technologies, strategies, and tactics while engaging in questions poised to overturn the foundations of modern political thought. Beginning with his personal experience training U.S. Marine recruits, he gleans insights from realist philosophy, the new materialism, and computational theory to show how the human being has been reconstituted from neutral citizen to unwitting combatant"--